Hubungan Ketuban Pecah Dini dengan Kejadian Asfiksia Neonatorum di RSUD H. Abdoel Madjid Batoe Batang Hari, Jambi - Bella Fitri Ayu; Syahrizal Syarif (Jurnal Medika Hutama, 2021)
Neonatal Asphyxia is one the main causes of neonatal mortality in Indonesia with a percentage of 27%. Premature rupture of membranes (PROM) is one of the factors that cause of nenonatal asphyxia. PROM causes oligohydramnios which compresses the umbilical cord so that it is narrowed and the blood flow that carries oxygen to the fetus is blocked, causing asphyxia. The purpose of this study was to determine the association between PROM and neonatal asphyxia. This study used a retrospective cohort study design. The samples of this study were are pregnant mothers who perform labor in Regional Public Hospital H. Abdoel Madjid Batoe Batang Hari, Jambi in 2020 selected based on simple random sampling method of 70 samples consisting of 35 exposed and 35 controls. The statistical test used is the multiple cox regression test with the risk factor model. There is association between PROM and neonatal asphyxia (RR= 4,34; 95% CI= 1,15 – 16,41, p-value=0,031) after controlled by gravidity, gestational age, anemia, preeclampsia, and birth weight. Based on study results, it is recommended for pregnant mother to consume vitamin C 100 mgper day to prevent PROM, carry out routine antenatal care, maintain blood pressure within normal ranges by paying attention to the food consumed, mangement and stress control, and consult a doctor before planning a pregnancy, especially for mothers who planned a second pregnancy for their second child and so on.